Peran Lutein dan Zeaxanthin dalam Formulasi AREDS 2: Mekanisme Protektif dan Implementasi Klinis pada Age-Related Macular Degeneration: Tinjauan Pustaka - Endy Juli Anto; Rusli, Kenvin (PT Kalbe Farma Tbk., 2026)
Lutein and zeaxanthin are carotenoids that serve as key components in the Age-Related Eye Disease Study 2 (AREDS 2) formulation, replacing beta-carotene from the original formulation due to safety concerns. These carotenoids exhibit dual protective mechanisms as blue light filters and antioxidants within the macula. This literature review aims to analyze the specific roles of lutein and zeaxanthin in AREDS 2, their molecular protective mechanisms, and their optimal clinical implementation in age-related macular degeneration (AMD). Literature searches were conducted through PubMed, Cochrane Library, and Google Scholar using the keywords